The late Roman world and its historian : interpreting Ammianus Marcellinus - Drijvers, Jan Willem; Hunt, David (Edward David), 1947- (Routledge classical monographs., 1999)
Ammianus Marcellinus, Greek by birth but writing in Latin c. AD 390, was the last great Roman historian. His writings are an indispensable basis for our knowledge of the late Roman world.